Advances in imaging and the management of myeloma bone disease - Terpos, E.; Moulopoulos, L.A.; Dimopoulos, M.A. (Journal of Clinical Oncology, 2011)
Osteolytic disease is a major complication of multiple myeloma that may lead to devastating skeletal-related events (SREs). Conventional radiography remains the gold standard for the evaluation of bone disease in patients with myeloma. However, whole-body magnetic resonance imaging (MRI) is recommended in patients with normal conventional radiography and should be performed as part of staging in all patients with a solitary plasmacytoma of bone. Urgent MRI is also the diagnostic procedure of choice to assess suspected cord compression, whereas computed tomography can guide tissue biopsy. Positron emission tomography with computed tomography can provide complementary information to MRI, but its use in multiple myeloma must be better defined by further studies. The incorporation of abnormal MRI findings into the definition of symptomatic myeloma also needs to be clarified. Bisphosphonates remain the cornerstone for the management of myeloma bone disease. Intravenous pamidronate and zoledronic acid are equally effective in reducing SREs, whereas zoledronic acid seems to offer survival benefits in symptomatic patients. Caution is needed to avoid adverse events, such as renal impairment and osteonecrosis of the jaw. Novel antiresorptive agents, such as denosumab, have given encouraging results, but further studies are needed before their approval for managing myeloma bone disease. Combination approaches with novel antimyeloma agents, such as bortezomib (which has anabolic effects on bone) with bisphosphonates or with drugs that enhance osteoblast function, such as antidickkopf-1 agents, antisclerostin drugs, or sotatercept, may favorably alter our way of managing myeloma bone disease in the near future. © 2011 by American Society of Clinical Oncology.